THE IMPACT OF THE PLATFORM ECONOMY (MARKETPLACE) ON NATIONAL MARKET DEVELOPMENT - Ashurov Hoshimjon Otayevich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
The rapid expansion of the platform economy, particularly marketplace models, has significantly transformed national market dynamics. This study examines the mechanisms through which digital marketplaces influence market efficiency, inclusivity, competition, and institutional structures. By reducing transaction costs, facilitating direct interactions between producers and consumers, and broadening access for small and medium-sized enterprises, marketplace platforms enhance national economic performance and stimulate innovation. The analysis highlights both the opportunities and challenges associated with the platform economy, including regulatory adaptation, market concentration, and data governance. Overall, marketplace platforms emerge as critical drivers of sustainable national market development and economic modernization.